Leakage current conduction mechanism of three-dimensional capacitors embedded in through-silicon vias. (30th May 2018) - Lin, Ye; Tan, Chuan Seng
Abstract: Leakage current conduction mechanism of three-dimensional capacitors embedded in through-silicon vias has been investigated for two sets of test vehicles, namely "sputtering samples" and "atomic layer deposition (ALD) samples". Schottky emission, hopping conduction, Poole–Frenkel emission, and Fowler–Nordheim tunneling have been identified for these samples, respectively. Self-consistent parameters are extracted through the analysis of leakage current conduction mechanisms: (1) optical dielectric constant (1.98–3.69), and (2) Schottky barrier height (1.66–2.21 eV). In terms of leakage current density, the ALD process is preferred over the sputtering process during the fabrication because the sputtered electrodes result in more traps in the vertical dielectric layers.